KAJIAN REPRESENTASI MASKOT DKI JAKARTA "ELANG BONDOL" DALAM MEDIA (STUDI KASUS "MOMO" - ASIAN PARA GAMES 2018) - Diean Arjuna D; Waridah Muthi'ah (Narada : Jurnal Desain dan Seni, 2019)
The Bondol eagle which has been clutching Salak Condet has been established as the Jakarta mascot since 1989. Unfortunately, this fact is not widely known by the public. In fact, most people assume that capital mascot is other icons that are far more popular, such as Monas and Ondel-Ondel. Apart from being caused by the decline in the flora and fauna resistance because the area is affected by development, one reason for the low popularity of the two mascots is the lack of representation of both of them in objects that are closely related to people's daily lives. This mascot was once the TransJakarta logo and is often present in batik motifs and posters, but is now rarely found. The latest application of this mascot actually comes in the form of Momo, the 2018 Asian Para Games mascot. Although it is not a special event held by the local government, in that representation, the Bondol eagle comes with the identity of Jakarta as one of the organizing cities. This research attempts to examine this phenomenon from the perspective of semiotics. The research is devoted to the representation of the Bondol eagle in various graphic media and visual communication related to the 2018 Asian Para Games, using descriptive-analytical methods. It is hoped that this research can become one of the references in the discussion and development of the Jakarta mascot in the media. The study was conducted with a descriptive qualitative method with a semiotics and shape morphology approach.